Human Resources Management in Higher Education Institutions in Poland = Zarządzanie zasobami ludzkimi w szkołach wyższych w Polsce - Szelągowska-Rudzka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The paper presents the diagnosis of the human resources management in Polish higher education institutions. The analysis of source literature was applied as a research method. The essence and components of HRM in connection with the university management system were discussed, the theoretical solutions, including those resulting from the provisions of the Law, and their practical implementations, were given a broad outline.
Keywords: zarządzanie zasobami ludzkimi; strategia personalna; strategia rozwoju; szkoły wyższe; system zarządzania uczelnią; human resources management (HRM); personnel strategy; development strategy; higher education institutions; university management system